Simulium (Trichodagmia) (Diptera, Simuliidae) phylogeny revisited: the Neotropical and Afrotropical connection - Molina, Óscar S.; Gil-Azevedo, Leonardo H. (European Journal of Taxonomy, 2021)
Simulium (Trichodagmia) Enderlein, 1934 has an unstable classification system. The broader concept of the subgenus includes five species-groups resulting from an extensive history of synonymisations, often outside of a phylogenetic framework. This concept also ignores relationship hypotheses with the Afrotropical subgenera S. (Anasolen) Enderlein, 1930, S. (Freemanellum) Crosskey, 1969, S. (Xenosimulium) Crosskey, 1969, and the Oviedoi species-group, with several Neotropical species of S. (Trichodagmia). We performed a morphological phylogenetic analysis to test the monophyly of S. (Trichodagmia), its species-groups, and their relationship with the above-mentioned subgenera and Oviedoi species-group. We analysed a data matrix with 69 terminal taxa and 62 characters under parsimony implied weights, with a range of concavities (k1–100), finding three categories of k. Our analysis concludes that S. (Trichodagmia) is not monophyletic, since Oviedoi and the Afrotropical subgenera group with its species-groups Tarsatum and Orbitale. Therefore, we propose a new classification for S. (Trichodagmia) by restricting it to the Orbitale species-group, revalidating S. (Hearlea) Vargas et al., 1946, S. (Hemicnetha) Enderlein, 1934, S. (Obuchovia) Rubtsov, 1947 and S. (Shewellomyia) Peterson, 1975, synonymysing S. (Xenosimulium) with S. (Anasolen), and erecting a new subgenus, S. (Disculter) subgen. nov. for Oviedoi. The geographical distribution of the groups involved is discussed.